The use of cannabinoids in the treatment of attention deficit hyperactivity disorder - a review of the latest literature - Skubel, Tomasz; Czarnota, Jakub; Dobrzyński, Michał; Kopystecka, Agnieszka; Kozioł, Ilona; Drozd, Małgorzata; Rybak, Natalia; Patryn, Rafał (Journal of Education, Health and Sport, 2022)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a common problem in adolescents and adults around the world. ADHD is particularly characterized by inattention, impulsiveness and hyperactivity, and in order to deal with these problems, patients often resort to other methods of treatment in addition to classic pharmacotherapy. Increasing numbers of ADHD patients are self-medicating with cannabis, despite the lack of specific evidence on its efficacy and safety. Aim of the study: The purpose of this study was to review the most recent available literature on the use of cannabidiol in the treatment of ADHD. For this purpose, PubMed and scopus databases were reviewed. The phrase "cannabidiol and ADHD" was used in the database search. After reviewing the titles and abstracts, 15 articles and articles cited in them were obtained and analyzed in detail. Results: Cannabinoids are reported to have pharmacological anxiolytic, neuroprotective, antidepressant, antipsychotic and hypnotic effects. Single-case studies of patients treated with them show that cannabinoids reduced hyperactivity, improved focus and control of impulsive behavior. Patients also reported side effects of cannabis use, the most common being mild short-term memory problems, dry mouth, sleepiness, and occasional experiences of constant thirst and greater forgetfulness. Most of the acute side effects were related to neuropsychiatric symptoms and were associated with cardiac sympathomimetic effects Conclusion: There is evidence for the effects of cannabinoids on ADHD symptoms as well as the influence of the cannabinoid system on involvement in neurological and psychiatric disorders. However, more controlled clinical trials are needed to determine the effect of cannabis use on ADHD symptoms and the norms of its use in this indication.